Cost of treating Insulin-requiring diabetes in children and adolescents - Onyiriuka, N; Ezomo, OO; Onyiriuka, RC (Journal of Institute of Medicine Nepal, 2013)
Background: Childhood diabetes care imposes a heavy economic burden on the patient’s family and all those involved in the provision of this care need to be aware of what factors drive cost. Methods: Using an interviewer-administered questionnaire data was obtained from eleven respondents (parents of diabetic children) on their expenditure on items of direct cost such insulin, syringes, cotton wool, methylated spirit, transportation, consultation, and glucometer with the test strips. Data was also obtained on income of the household, ability to cope with payment for medical care and sources of money used for such payment. Results: The estimated mean monthly direct cost of routine diabetes care was ten thousand nine hundred and fifty Naira [(N10,950+4,698); 95% Confidence Interval, CI = 8,674-13,726] with purchase of insulin accounting for 51.1% of this cost. Money spent on purchase of insulin alone represented 43.7% of the average monthly household income. Eighty percent of the parents expressed varying degrees of difficulty coping with payment of direct cost of diabetes care. Conclusion: Insulin-requiring diabetes imposes a heavy economic burden on the family of the patient with cost of purchase of insulin contributing the highest proportion among items of direct cost. DOI: http://dx.doi.org/10.3126/joim.v34i1.9115 Journal of Institute of Medicine, April, 2012; 34:1 2-8